Here my attempts for integrating $\cos^4(x)$ in few methods.

1st method.





So, $\int\cos^4xdx=\int(\cos^2x)^2dx$



2nd method.

By using reduction formula, $\cos^4xdx=\frac{1}{4}\sin x\cos^3x+\frac{3}{4}\int\cos^2xdx$

$=\frac{1}{4}\sin x\cos^3x+\frac{3}{4}\int(\frac{1}{2}\cos2x+\frac{1}{2})dx$

$=\frac{1}{4}\sin x\cos^3x+\frac{3}{8}\int\cos2x+\frac{3}{8}\int1dx$

$=\frac{1}{4}\sin x\cos^3x+\frac{3}{16}\sin 2x+\frac{3}{8}x$

$=\frac{1}{4}\sin x \cos^3x+\frac{3}{8}\sin x \cos x+\frac{3}{8}x$

3rd method, By using De Moivre's formula.

4th method

$\int \cos^4xdx=\int (\frac{e^{ix}+e^{-ix}}{2})^4dx$

$=\frac{1}{16}\int (e^{4ix}+4e^{2ix}+6+4e^{-2ix}+e^{-4ix})dx$

$=\frac{1}{16}\int (e^{4ix}+e^{-4ix}+4(e^{2ix}+e^{-2ix})+6)dx$



$\frac{1}{16}(\frac{1}{2}\sin 4x+4\sin 2x+6x)+c$

$\frac{1}{8}(\frac{1}{4}\sin 4x+2\sin 2x+3x)+c$

I want to ask is there more method to integrate it? Thanks.

  • $\begingroup$ If you know how to integrate $ \sin^{2} $, then you’re done because \begin{align} {\cos^{4}}(x) & = {\cos^{2}}(x) \cdot \left[ 1 - {\sin^{2}}(x) \right] \\ & = {\cos^{2}}(x) - {\cos^{2}}(x) \cdot {\sin^{2}}(x) \\ & = {\cos^{2}}(x) - \frac{1}{4} [2 \sin(x) \cos(x)]^{2} \\ & = \left[ 1 - {\sin^{2}}(x) \right] - \frac{1}{4} {\sin^{2}}(2 x). \end{align} $\endgroup$ – Berrick Caleb Fillmore Apr 23 '15 at 7:51
  • $\begingroup$ I think you've covered all the obvious methods unless you want to express it as a power series and integrate term by term...................... $\endgroup$ – Mathemagician1234 Apr 23 '15 at 7:56
  • $\begingroup$ @Mathemagician1234: The OP wants to hack this problem into pieces. $\endgroup$ – Berrick Caleb Fillmore Apr 23 '15 at 7:59
  • $\begingroup$ $cos^2(x)=\frac {1+cos(2x)}2$ and $sin^2(x)=\frac {1-cos(2x)}2$ Then $cos^4(x)=\frac {1+cos(2x)}2 - \frac 14 \frac {1-cos(4x)}2$ $\endgroup$ – user128766 Apr 23 '15 at 8:06
  • $\begingroup$ @Mathemagician1234 I don't know why. Whenever I solving problem, I will have to know methodss to solve it. $\endgroup$ – Mathxx Apr 23 '15 at 8:18

Let us first establish a general formula, with an obvious notation:

$$(C^cS^s)'=-cC^{c-1}S^{s+1}+sC^{c+1}S^{s-1}=-cC^{c-1}(1-C^2)S^{s-1}+sC^{c+1}S^{s-1}\\ =-cC^{c-1}S^{s-1}+(s+c)C^{c+1}S^{s-1}.$$

Then, rewriting and shifting the indexes,

$$\int C^\color{green}cS^s\,dx=\frac1{s+c}C^{c-1}S^{s+1}+\frac{c-1}{s+c}\int C^{\color{green}{c-2}}S^s\,dx.$$

Then $$C^2\to\frac12CS+\frac12x,$$ $$C^4\to\frac14C^3S+\frac34\left(\frac12CS+\frac12x\right).$$

Deriving $C^{c-1}S$ directly leads to the recurrence $$\int C^\color{green}c\,dx=\frac1cC^{c-1}S+\frac{c-1}c\int C^{\color{green}{c-2}}\,dx.$$


I think you gave the most straightforward methods, including the sure-to-success replacement by $e^{ix}+e^{-ix}$. Basically any other method is going to be a more obfuscated form of this one.

You could also give a shot to the rational parametrization of the unit circle, by using $\cos x = \frac{1-t^2}{1+t^2}$ and $dx = \frac{2\,dt}{1+t^2}$, so that $\int \cos^4 x dx = \int \frac {2(1-t^2)^4dt}{(1+t^2)^5}$, expanding this ugly rational fraction at the poles, and then reusing the rational parametrization to fall back on the trigonometric result.

There might also be a way to do this using Fourier expansion, but I'm not sure I want to see this.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.